DETECTION OF SERUM MACRO MINERALS CONCENTRATION IN REPEAT BREEDING ACEH CATTLE - Thasmi, Cut Nila; Husnurrizal, Husnurrizal; Akmal, Muslim; Wahyuni, Sri; Siregar, Tongku Nizwan (Universitas Syiah Kuala, 2020)
The purpose of this study was to determine the macro minerals concentration in serum of repeat breeding (RB) Aceh cattle. In this study 16 Aceh cattle were examined; they consisted of 7 fertile Aceh cattle (P1) and 9 Aceh cattle with RB (P2), all of which were 3-8 years old with abody condition score (BCS) of 3-4. Serum collection was carried out for examining the level of serum minerals, including magnesium, phosphorus, sodium, potassium, chloride, and calcium. Data was analysed using T-test. The levels of magnesium, phosphorus, sodium,potassium, chloride, and calcium in P1 vs P2 were 2.180.60 vs. 2.200.34 mg/dL; 6.181.34 vs. 6.480.74 mg/dL; 142.715.09 vs.142.442.29 mmol/L; 4.810.76 vs. 4.760.51 mmol/L; 104.574.35 vs. 107.677.36 mmol/L; and 9.070.45 vs. 9.90 0.60 mg/dL (P0.05), respectively. It was concluded that the concentration of serum macro minerals do not affect the incidence of RB in Aceh cattle.